ROLE OF ORGANIC, BIO AND MINERAL FERTILIZERS IN ENVIROMENTAL SUSTAINABILITY AND ENHANCING LETTUCE PRODUCTIVITY - J. M. Mahmood; W. M. Al-Joboory; I. A. Abed (مجلة الأنبار للعلوم الزراعية)
This field experiment was conducted during the fall season of 2023 at Research Station 1, an affiliate of the College of Agriculture, University of Anbar. Three factors were used: organic fertilizer at two levels (1 and 2%), bacterial isolates (Bacillus megaterium + Azotobacter chroococcum and Stenotrophomona maltopilia), and mineral fertilizer at levels of 100, 75, 50 and 25%, in a randomized complete block design (RCBD) with three replicates. The results demonstrate the capability of bacterial isolates along with organic material to increase NPK availability in soil as well as optimize the yields and production of lettuce. Interaction treatment exceeded others by increasing N and P concentrations, with total yields and number of phosphate-dissolving and nitrogen-fixing bacteria attaining 133.61 mg N kg-1, 29.67 mg P kg-1, 61.38 Mg. h-1, 7.843 log cfu. g-1 soil, and 6.962 log cfu g-1 soil, respectively. In addition to providing the lettuce plant with nutrition it reduced the amount of added mineral fertilizers by 50% from the recommended amount. It also achieved a positive role in reducing the concentration of nitrates in the lettuce leaves.